Kewenangan Mahkamah Konstitusi Dalam Memutus Perkara Open Legal Policy Menurut Sistem Ketatanegaraan Indonesia - T. Emadjaik, Mario; Yohanes, Saryono; G. Tuba Helan, Yohanes (Journal of Comprehensive Science, 2024)
The issue of the Constitutional Court's authority in assessing a decision related to open legal policy has become a very interesting discussion and has received a lot of attention from the public. As explained above, when rejecting a case, the Constitutional Court always argues that the case is an open legal policy, which is the authority of the DPR as the legislator. In several recent decisions, the Constitutional Court has been inconsistent in viewing and adjudicating cases that have an open legal policy nuance. One example of the court being inconsistent in the decisions it makes is regarding the election law regarding age limits, which has recently become a legal debate. The Constitutional Court as the guardian and interpreter of the constitution or “the guardian and the sole and the highest interpreter of the constitution” in several of its decisions regarding age in elections, it provides its interpretation contained in various decisions related to open legal policies made by legislators. Therefore, the formulation of the problem contained in this research is how to regulate the authority of the Constitutional Court in reviewing laws related to open legal policy and what are the legal implications of the authority of the Constitutional Court in deciding cases related to open legal policy. The research used in this writing uses normative legal research. This research uses a statutory approach, a conceptual approach. The research results show that the authority of the constitutional court in deciding open legal policy cases is contrary to the authority possessed by the constitutional court and has implications for the concept of the division of power. The Constitutional Court must have a clear legal basis in looking at cases related to open legal policy so that in the future the constitutional court will have a clear perspective. the same so that there are no more inconsistencies in the Constitutional Court's decisions regarding cases that have an open legal policy nuance. Regulations regarding open legal policy must be regulated in detail so that the norm testing process carried out has clear standards and mechanisms so as to provide legal certainty for the community